Management of Low-Risk Papillary Thyroid Cancer - Nicole M. Iñiguez-Ariza; Juan P. Brito (Endocrinology and Metabolism, 2018)
The incidence of thyroid cancer has increased, mainly due to the incidental finding of low-risk papillary thyroid cancers (PTC). These malignancies grow slowly, and are unlikely to cause morbidity and mortality. New understanding about the prognosis of tumor features has led to reclassification of many tumors within the low-risk thyroid category, and to the development of a new one “very low-risk tumors.” Alternative less aggressive approaches to therapy are now available including active surveillance and minimally invasive interventions. In this narrative review, we have summarized the available evidence for the management of low-risk PTC.